2014
DOI: 10.1364/oe.22.012808
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired, sub-wavelength surface structures for ultra-broadband, omni-directional anti-reflection in the mid and far IR

Abstract: Quasi-ordered moth-eye arrays were fabricated in Si using a colloidal lithography method to achieve highly efficient, omni-directional transmission of mid and far infrared (IR) radiation. The effect of structure height and aspect ratio on transmittance and scattering was explored experimentally and modeled quantitatively using effective medium theory. The highest aspect ratio structures (AR = 9.4) achieved peak transmittance of 98%, with >85% transmission for λ = 7-30 μm. A detailed photon balance was construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…( b ) Adapted from Gonzalez and Gordon [77], Copyright 2014, with permission from OSA Publishing; ( d , e ) Adapted by permission from Macmillan Publishers Ltd.: Nature Communications, Siddique et al . [76], Copyright 2015.…”
Section: Figurementioning
confidence: 99%
“…( b ) Adapted from Gonzalez and Gordon [77], Copyright 2014, with permission from OSA Publishing; ( d , e ) Adapted by permission from Macmillan Publishers Ltd.: Nature Communications, Siddique et al . [76], Copyright 2015.…”
Section: Figurementioning
confidence: 99%
“…Recent studies have demonstrated that random antireflective structured surfaces (rARSS) can be used as an alternative to thin film coatings, reducing Fresnel reflections in the visible and the infrared (IR). [1][2][3][4][5][6][7][8] Broadband response, high transmission across wide ranges of angle of incidence (AOI), and polarization insensitivity have also been reported. 9,10 In general, the AR effects correlate with the density and depth of the nanostructures, simulating an effective medium gradient-index boundary profile, which reduces Fresnel reflectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the EMT predicts that better light entrapment will occur for larger pillar heights as long as p λ/ns. It was shown previously that transmission at long wavelengths is governed by the pillar height [17,18]. The height of the surface structures should be also sufficient to ensure a slowly varying volume fraction change.…”
Section: Introductionmentioning
confidence: 99%
“…The alumina taper-nanopores were used for preparing polymer AR coatings operating in visible and NIR range via template imprinting technique [18,25,26]. For an AR coating working at longer wavelengths, however, a larger pore spacing is needed [3,4,17]. Larger pore spacing means also the possibility to design tapered pores with a larger area of the cone base.…”
Section: Introductionmentioning
confidence: 99%